The Diachronic Approach to the Study of Rhythm in Shakespeare’s Performances - Лисенко, Катерина Вікторівна (Київський національний університет імені Тараса Шевченка, 2024)
The article explores the overall influence and creativity of W. Shakespeare, as well as changes in approaches to theatrical interpretations and performances of Shakespeare’s works from a diachronic perspective. The themes of Shakespeare’s works delve into the complexities of human relationships, ensuring their relevance to this day. The significance of Shakespeare’s dramas and comedies on contemporary literature cannot be overstated. Performances of Shakespeare’s works evolve over time, rendering them entirely modern. The article discusses a shift in approach to speech rhythm, adding different characteristics and melodiousness, eliciting positive reactions from the audience. The diachronic approach involves comparing various performances across different time periods. To investigate real changes in the prosody of Shakespearean performances, the authors examined chronologically different renditions of the same excerpts and compared their key indicators using modern computer programs. The conclusions indicate significant changes in pause lengths, speech rates, and the direction of the main tone. The role of rhythm in Shakespeare’s performances serves as an emotional foundation and an even stronger link connecting the actor and the audience.

У статті йдеться про вплив та творчість В. Шекспіра в цілому та про зміни в підходах до театральних підходів та виконань творів Шекспіра в діахронічному аспекті. Тематика творів В. Шекспіра торкається складнощів людських стосунків, і тому його доробки залишаються релевантними й досі. Неможливо переоцінити важливість впливу драм та комедій В. Шекспіра на сучасну літературу. Виконання Шекспірівських творів змінюється з часом, що робить їх абсолютно сучасними і модерними. В статті йдеться про зміну підходу до ритму мовлення, що додає інших рис та мелодійності і викликає позитивні реакції глядача. Діахронічний підхід має включати порівняння різних виконань в різні часові періоди. Для того, щоб дослідити реальні зміни в просодії виконань шекспірівських творів, автори дослідили хронологічно різні варіанти реалізацій однакових уривків, і за допомогою сучасних комп’ютерних програм порівняли основні їхні показники. Висновки свідчать про значні зміни у показниках пауз, швидкості мовлення та напрямку основного тону. Роль ритму в виставах В. Шекспіра служить немов би емоційною основою та ще міцнішим ланцюжком, який з’єднує актора та глядача.
Діахронічний підхід до вивчення ритму в постановках Шекспіра
Keywords: evolution; rhythm; development of performance styles; a symphony of tones and inflections; to preserve unique voices and manners of performers; rate of speech; a narrowed range of frequency of the main tone; localization of pauses; maximum duration of pauses; alliteration; repetition of consonants; platform for continual reinterpretation and innovation; еволюція; ритм; розвиток стилів виконання; симфонія тонів та інфлекцій; зберегти унікальні голоси та манеру виконання; швидкість мовлення; звужений діапазон частоти основного тону; розташування пауз; максимальна довжина пауз; алітерація; повторення приголосних; платформа для постійної реновації та інновації